Andrographolide Inhibits Static Mechanical Pressure-Induced Intervertebral Disc Degeneration via the MAPK/Nrf2/HO-1 Pathway - Zhang C; Lu Z; Lyu C; Zhang S; Wang D (Dove Medical Press, 2023)
Cunxin Zhang,1,2 Ziang Lu,3 Chaoliang Lyu,2 Shanshan Zhang,4 Dechun Wang1 1Department of Spine Surgery, Qingdao Municipal Hospital, Shandong University, Qingdao, 266061, People's Republic of China; 2Department of Spine Surgery, Jining No.1 People's Hospital, Jining, 272011, People's Republic of China; 3Jining Medical University, Jining, 272067, People's Republic of China; 4Department of Neurology, Jining No.1 People's Hospital, Jining, 272011, People's Republic of ChinaCorrespondence: Dechun Wang, Department of Spine surgery, Qingdao Municipal Hospital, Shandong University, 5# Donghai Road, Shinan District, Qingdao, 266061, People's Republic of China, Tel +86+18661809296, Fax +86-0532-82716868, Email dechun-w@163.comPurpose: To explore the molecular mechanism by which andrographolide (ADR) inhibits static mechanical pressure-induced apoptosis in nucleus pulposus cells (NPCs) and to assess the role of ADR in inhibiting IDD.Methods: Hematoxylin-eosin (HE), toluidine blue, and immunofluorescence staining were used to identify NPCs. An NPC apoptosis model was constructed using a homemade cell pressurization device. The proliferation activity, reactive oxygen species (ROS) content, and apoptosis rate were detected using kits. The expression of related proteins was detected using Western blot. A rat tailbone IDD model was constructed using a homemade tailbone stress device. HE staining and safranine O-fast green FCF cartilage staining were used to observe the degeneration degree of the intervertebral disk.Results: ADR inhibits static mechanical pressure-induced apoptosis and ROS accumulation in NPCs and improves cell viability. ADR can promote the expression of Heme oxygenase-1 (HO-1), p-Nrf2, p-p38, p-Erk1/2, p-JNK, and other proteins, and its effects can be blocked by inhibitors of the above proteins.Conclusion: ADR can inhibit IDD by activating the MAPK/Nrf2/HO-1 signaling pathway and suppressing static mechanical pressure-induced ROS accumulation in the NPCs.Keywords: andrographolide, intervertebral disc degeneration, nucleus pulposus cells, apoptosis, reactive oxygen species, HO-1